2017
DOI: 10.1021/acsami.7b12784
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Nickel Oxide Hole Contact Layers: Work Function versus Conductivity

Abstract: Nickel oxide (NiO) is a widely used material for efficient hole extraction in optoelectronic devices. However, its surface characteristics strongly depend on the processing history and exposure to adsorbates. To achieve controllability of the electronic and chemical properties of solution-processed nickel oxide (sNiO), we functionalize its surface with a self-assembled monolayer (SAM) of 4-cyanophenylphosphonic acid. A detailed analysis of infrared and photoelectron spectroscopy shows the chemisorption of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 69 publications
1
31
0
2
Order By: Relevance
“…17 Recently, NiO x layers, obtained through a sol-gel process from nickel organic salts precursors, have been successfully utilized in organic (OPV) and perovskite photovoltaic devices, showing improved device performance and stability. [18][19][20][21][22][23][24] However, the used sol-gel process required a high temperature treatment (250-400 C) to induce the decomposition of the precursor into a crystalline NiO x nanoparticle (NP) layer followed by a plasma treatment which further oxidizes the nanoparticles. The latter treatment enhances the non-stoichiometry of mixed nickel oxidation states, and, in-turn, the layer's conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently, NiO x layers, obtained through a sol-gel process from nickel organic salts precursors, have been successfully utilized in organic (OPV) and perovskite photovoltaic devices, showing improved device performance and stability. [18][19][20][21][22][23][24] However, the used sol-gel process required a high temperature treatment (250-400 C) to induce the decomposition of the precursor into a crystalline NiO x nanoparticle (NP) layer followed by a plasma treatment which further oxidizes the nanoparticles. The latter treatment enhances the non-stoichiometry of mixed nickel oxidation states, and, in-turn, the layer's conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Surface modification is a simple way to varify the surface properties of thin films, such as work function, wettability and so on . Self‐assembled monolayers (SAMs) are the most popular techniques to modify the surface properties of carrier transport layers.…”
Section: Modified Niox Films For Pscsmentioning
confidence: 99%
“…Apparently, NiO shows a significant PL quenching, indicating holes extraction and transfer at NiO/perovskite interface effectively. To understand the behaviour of NiO film that has been oxidized at 450 °C and its apparent effective extraction of holes from perovskite film, we need to consider the study which has been carried by S. Hietzschold et al about the effect of annealing temperature on the work function of NiO films [33]. They have shown that the work function of NiO films at 400 °C was less than the work function at 325 °C, which promote the carrier extraction of NiO film.…”
Section: Optical Properties Of Niomentioning
confidence: 99%